Biodegradation of Extractable Petroleum Hydrocarbons by Consortia Bacillus cereus and Pseudomonas putida in Petroleum Contaminated-Soil - Abubakar Tuhuloula; Suprapto Suprapto; Ali Altway; Sri Rachmania Juliastuti (Indonesian Journal of Chemistry, 2019)
Contamination of soil by the activities of exploration, production, and disposal of oil waste into the environment causes serious damage to the environmental ecosystem, the target of processing by the bacteria as a model for remediation of oil contaminated site. Thus, the study was focused on determining the biodegradation percentage of extractable petroleum hydrocarbons as a function of the oil concentration. This research was conducted in a slurry bioreactor with mixed contaminated soil to water ratio of 20:80 (wt.%). A consortium of Bacillus cereus and Pseudomonas putida bacteria 10% (v/v) and 15% (v/v) with the ratio of 2:3, 1:1, and 3:2 was inserted into the slurry bioreactor and a single reactor was used as a control. The result of identification with an initial concentration of extractable petroleum hydrocarbons of 299.53 ng/µL, after 49 days of incubation for bacterial consortium 10% (v/v), the concentration was reduced to 85.31; 32.43; 59.74; and 112.22 ng/µL respectively and the biodegradation percentage was 71.5; 89.17; 80.05; and 62.54%. As for the bacterial consortium concentration of 15% (v/v) with the same ratio and control, the effluent concentration was 12.48; 7.72; 18.93 ng/µL, respectively or the biodegradation percentage was 95.83; 97.42; 93.68%.